2019
DOI: 10.1007/s12105-019-01043-z
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Receptor B1 and C-Reactive Protein as Prognostic Factors for Pharyngocutaneous Fistula Development After Laryngectomy

Abstract: Pharyngocutaneous fistulae (PCF) are one of the most common complications after laryngectomy. Predisposing risk factors have been studied, yet knowledge to determine which patients are prone to developing a fistula remains scarce. This study aims to establish prognostic parameters to identify individual patients at risk for PCF development. As PCF and inflammation seem to be interwoven, this work focuses on markers able to detect an inflammatory response. We retrospectively analyzed all patients who had underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…One study reported that, the application of platelet‐rich fibrin (PRF) in suture repair of the pharynx reduces the incidence of PCF; PRF influences the expression of various cytokines and growth factors 32 . Another report revealed that the expression of bradykinin 1 receptor, which plays an important role in the inflammatory response, is a risk factor for PCF 33 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One study reported that, the application of platelet‐rich fibrin (PRF) in suture repair of the pharynx reduces the incidence of PCF; PRF influences the expression of various cytokines and growth factors 32 . Another report revealed that the expression of bradykinin 1 receptor, which plays an important role in the inflammatory response, is a risk factor for PCF 33 …”
Section: Discussionsupporting
confidence: 92%
“…32 Another report revealed that the expression of bradykinin 1 receptor, which plays an important role in the inflammatory response, is a risk factor for PCF. 33 In a study by Aires et al involving 157 patients with squamous cell carcinoma of the larynx, patients with NLR >2.5, exhibited a higher risk of developing PCF after total laryngectomy. 9 Our results corroborate this finding.…”
Section: Discussionsupporting
confidence: 88%
“…Koob et al 2 recently reported that persistently elevated CRP beyond post‐operative day six was a risk factor for fistula formation after laryngectomy. However, there are limited data relating to CRP in head and neck surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngocutaneous fistula is a major post‐operative complication; one recent meta‐analysis reported the incidence at 21% 1 . Uncontrolled salivary leakage through the fistula results in infection, impaired wound healing, risk of saliva‐induced erosion of a major vessel, increased cost of treatment and has a negative effect on the patient's physical and psychological well‐being 2 . Studies have identified risk factors for fistula formation 1,3 but there is less research to identify those patients at risk of fistula formation, specifically for laryngectomy‐related neopharyngeal repairs.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of wound amylase concentration for early detection of PCF has been shown in many studies [10]. Koob and his colleagues described the role of Bradykinin Receptor B1 and C-reactive protein as prognostic factors for pharyngocutaneous fistula development after laryngectomy [11].…”
Section: Introductionmentioning
confidence: 97%